The Development of Interactive Multimedia Using Lectora Inspire Application in Arabic Language Learning - Adam Mudinillah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
Interactive learning media that were used in schools, in general, were still less innovative, only use the media available in the school environment, and do not utilize technology. The aim of this study developed interactive multimedia using Lectora Inspire application in learning Arabic Language class VII at Islamic Junior High School Thawalib Tanjung Limau. The goal to be achieved was to produce interactive multimedia using the Lectora Inspire application that was valid, practical, and effective. The researcher used Research and Development model. The results showed that interactive multimedia using the Lectora Inspire application in Arabic learning that was developed had met valid criteria with the characteristics of media content in accordance with the curriculum, design and layout that was clear, ease of operation of the media. The results of observations and questionnaires show that learning media were already practical with characteristics that have precise contents and goals. In addition, the developed media has also in increasing student activity and learning outcomes, with 85.8% mastery learning. Keywords: Lectora Inspire, Interactive Multimedia, Arabic